Seismic behavior of reinforced concrete porticoes under the influence of the strong portion in a soft soil (Gaceta Técnica, 2014)
The soil maximum acceleration is one of most widely used seismic disturbance parameters and it is associated with the earthquake destructive potential. However, there is no direct relationship between them since some earthquakes with large maximum accelerations do not cause further damage, recognizing that the acceleration maximum amplitude is a poor indicator of an earthquake destructive potential. Due to the earthquake complexity, it is not easy to define parameters which are able to obtain the strong portion of any seismic event to assess its behavior in reinforced concrete structures. For that reason, a definition to get the amount of portion considered as strong earthquake is previously needed. Nevertheless, this is performed using log-acceleration time history and its respective acceleration elastic response spectrum used to determine the stronger portion of the physical phenomenon
Keywords: accelerogram; soft soil; strong portion